New grape stems-based liqueur: Physicochemical and phytochemical evaluation. (1st January 2016) - Barros, Ana; Gouvinhas, Irene; Machado, Nelson; Pinto, Joana; Cunha, Maria; Rosa, Eduardo; Domínguez-Perles, Raúl
Highlights: New grape stems-based liqueur as sustainable valorization of vinification residues. Changing (poly)phenolic content at 90 and 180 days of maceration. Profiling phytochemicals showed that 90 days of maceration was optimal. Positive correlation between phenolic composition and antioxidant activity. Abstract: A number of traditional liqueurs are obtained by maceration of red fruits in aqueous ethanol liquor, namely sloe berries or sour cherry. On the other hand, the exploration of residual plant material derived from the winery industry (grape ( Vitis vinifera L.) stems), which has been regarded as an interesting source of colored and uncolored (poly)phenols, could lead to an industrial alternative to the traditional distilled spirits produced, with valuable physicochemical and phytochemical properties. In the present work, vinification residues (grape stems) were used to produce a new beverage. The evaluation of the physic-chemical characteristics and phytochemical composition as well as the evolution of the determined parameters during maceration (90 and 180 days) allowed a number of interesting bioactive compounds to be identified. This new beverage is a liqueur with a high retention of phenolic compounds ( ortho -diphenols, flavanols, flavonols, and anthocyanins), with interesting physic-chemical characteristics, that revealed significant antioxidant activity.